Antibacterial and Anticancer Potentials of Presynthesized Photosensitive Plectranthus cylindraceus Oil/TiO2/Polyethylene Glycol Polymeric Bionanocomposite. (31st October 2021) - Amina, Musarat; Al Musayeib, Nawal M.; Alarfaj, Nawal A.; El-Tohamy, Maha F.; Al-Hamoud, Gadah A.
Abstract : The present study is concerned with the fabrication of the bifunctional Plectranthus cylindraceus oil/TiO2 /polyethylene glycol polymeric film for antibacterial and anticancer activities. The suggested film is based on the utility of naturally extracted P. cylindraceus oil in the formation of the polymeric bionanocomposite film decorated with TiO2 nanoparticles. The bionanocomposite film was fabricated by incorporating 15 w% of P. cylindraceus oil with 10 w% polyethylene glycol and 5 w% TiO2 nanoparticles. The active components of P. cylindraceus oil were verified using gas chromatography coupled with mass spectrometry (GC-MS). The surface morphology of the resulted bionanocomposite film was characterized by various spectroscopic and microscopic techniques. The antibacterial potential of the fabricated bionanocomposite film was investigated against four pathogenic strains. The obtained results revealed excellent sensitivity against the bacterial strains, particularly E. coli and S. aureus, with minimum inhibitory concentration 320  µ g mL −1 and minimum bactericidal concentration 640 and 1280  µ g mL −1 for E. coli and S. aureus, respectively. Polymeric bionanocomposite exerted significant cytotoxicity against human lung carcinoma cell lines in a concentration-dependent manner with an IC50 value of 42.7 ± 0.25  μ g mL −1 . Safety assessment test against peripheral blood mononuclear cells (PBMCs) demonstrated that the bionanocomposite is nontoxic in nature. Bionanocomposite also showed potent photocatalytic effects. Overall, the results concluded that the bionanocomposite has expressed scope for multifaceted biomedical applications.